2001
DOI: 10.1021/ja0108786
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Ions on the Dynamics and Structure of Single-Stranded DNA Oligomers:  A Molecular Dynamics Study

Abstract: The effects of sodium counterion presence and chain length on the structure and dynamics of single DNA strands of polythymidylate were studied by means of molecular dynamics simulations. The importance of the base-base stacking phenomenon increases with the chain length and partially reduces the flexibility of the strand. Sodium ions directly interact with the phosphate groups and keto oxygens of the thymine bases, complexes showing lifetimes below 400 ps. Simultaneous phosphate and keto complexes were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 67 publications
13
62
1
1
Order By: Relevance
“…There are two peaks in g(r), one centered at 2.15Å corresponding to contact between the Na + ion and the oxygen, and a second peak near 3.95Å, corresponding to the first hydration shell of the Na + ion. The location of the first peak is about the same as was seen in previous MD simulations of ssDNA oligomers [37,38], but the second peak occurs for smaller r, presumably because there are fewer steric constraints in the NMPs than in a ssDNA strand. The very large magnitudes of the peaks demonstrate the high probability that a Na + ion will be found near one or more of the phosphate oxygens.…”
Section: Ion Association Dynamicssupporting
confidence: 76%
“…There are two peaks in g(r), one centered at 2.15Å corresponding to contact between the Na + ion and the oxygen, and a second peak near 3.95Å, corresponding to the first hydration shell of the Na + ion. The location of the first peak is about the same as was seen in previous MD simulations of ssDNA oligomers [37,38], but the second peak occurs for smaller r, presumably because there are fewer steric constraints in the NMPs than in a ssDNA strand. The very large magnitudes of the peaks demonstrate the high probability that a Na + ion will be found near one or more of the phosphate oxygens.…”
Section: Ion Association Dynamicssupporting
confidence: 76%
“…However, recent calculations have indicated that these short DNAs might exhibit a tendency for formation of bent structures [19]. It might thus be possible that the location-dependent kinetics is a combined result of (1) a varying tendency for cation accumulation along the oligomer and (2) the formation of a transient, bent structure facilitating interaction with the middle positions [19,52,53,54,55,56,57]. Comparison of present data with those obtained for interactions with the phosphorothioate group shows clearly that binding to the non-charged bases is less influenced by a variation of location of the binding site in the DNA environment.…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…Further, the reduced reaction rates and magnitude of the electrostatic interactions observed after a change of Na + for Mg 2+ in the supporting electrolyte supports a mechanism where the charged platinum complex replaces a cation in the condensation layer surrounding the oligomers. The influence on kinetics from exchange of surface bound bulk cations for the platinum complex seems reasonable, considering the close proximity of the electrostatically preferred interaction sites along the phosphodiester backbone and the reactive phosphorothioate group [5,6,17,18,19]. The present study has been designed to obtain information on how the kinetics is influenced by a translocation of the reactive group from the charged backbone to the non-charged bases.…”
Section: Introductionmentioning
confidence: 99%
“…The counter ions of Na + , Mg 2+ , K + and Cl -were used in modeling at the same concentrations as in the AF4 carrier solution to mimic the actual solution environment for the ssDNAs. After energy minimization of the starting molecule structure, 1000 picoseconds (ps) equilibration without restraints was performed with constant pressure and the periodic boundaries maintained by the particle mesh Ewald method, [42] while the volume of the box was allowed to change. The simulated 3D structure allowed the measurement of d xyz of each atom, which was the distance from the atom to the center of mass of all selected atoms.…”
Section: Molecular Dynamics (Md) Simulation and Folded Percentage Calmentioning
confidence: 99%
“…[41][42][43] To evaluate the ssDNA structure stability during the simulation, the root-mean-squared deviation (RMSD) of all heavy atoms of each ssDNA was obtained. Although we used a shorter simulation time, 1000 ps, than the 50 ns in the cited reports, [41][42][43] due to limitation of the total service units available to us from XSEDE, the RMSD values in the last 200 ps of the simulation typically had < 5% relative standard deviation (RSD), except for poly(dA) 10 , poly(dA) 20 , and the TA, the RSD of which varied between 8-10% (Supporting Information, Figure S3a). Still, the volume or bulkiness of all strands changed very little, shown by the fairly constant R g during the simulation duration (Supporting Information, Figure S3b).…”
Section: Properties Of Ssdnas Selected For the Studymentioning
confidence: 99%